2021
DOI: 10.1101/2021.01.14.21249839
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Innate lymphoid cells and disease tolerance in SARS-CoV-2 infection

Abstract: BACKGROUNDRisk of severe coronavirus disease 2019 (COVID-19) increases with age, is greater in males, and is associated with decreased numbers of blood lymphoid cells. Though the reasons for these robust associations are unclear, effects of age and sex on innate and adaptive lymphoid subsets, including on homeostatic innate lymphoid cells (ILCs) implicated in disease tolerance, may underlie the effects of age and sex on COVID-19 morbidity and mortality.METHODSFlow cytometry was used to quantitate subsets of bl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 124 publications
(300 reference statements)
1
23
0
Order By: Relevance
“…[28] Furthermore, innate immunity has been found to play an important role in the control of infection in coronavirus animal reservoirs and may similarly contribute to reduced severity of COVID-19 disease observed in children compared to adults. [29,30] Our study found a durable reduction in the risk of COVID-19 infection following receipt of RZV vaccine, consistent with the durable protection against heterologous infections provided by trained immunity. [9] It is possible that the AS01 adjuvant used in RZV, which activates innate immune responses including monocytes and the IFN-response pathways, may be associated with the reduced risk of COVID-19 diagnosis and hospitalization observed in this study.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…[28] Furthermore, innate immunity has been found to play an important role in the control of infection in coronavirus animal reservoirs and may similarly contribute to reduced severity of COVID-19 disease observed in children compared to adults. [29,30] Our study found a durable reduction in the risk of COVID-19 infection following receipt of RZV vaccine, consistent with the durable protection against heterologous infections provided by trained immunity. [9] It is possible that the AS01 adjuvant used in RZV, which activates innate immune responses including monocytes and the IFN-response pathways, may be associated with the reduced risk of COVID-19 diagnosis and hospitalization observed in this study.…”
Section: Discussionsupporting
confidence: 72%
“…[28] Furthermore, innate immunity has been found to play an important role in the control of infection in coronavirus animal reservoirs and may similarly contribute to reduced severity of COVID-19 disease observed in children compared to adults. [29, 30]…”
Section: Discussionmentioning
confidence: 99%
“…Silverstein et al corroborate these findings by establishing that a higher ILC abundance in the blood was associated with less time spent in the hospital. Further, hospitalized individuals with COVID-19 had 1.78-fold fewer ILCs in the blood (78). Taken together, these studies illustrate a correlation between decreased ILCs in the blood periphery and severe SARS-CoV-2 infection.…”
Section: Ilc3s In Viral Lung Infections With Implications For Covid-19mentioning
confidence: 58%
“…The role of total ILCs and specifically ILC1 in antiviral immune response has been previously shown [ 34 , 35 ]. A reduction of ILC1 in severe COVID-19 patients has been recently described by García et al [ 35 ].…”
Section: Discussionmentioning
confidence: 99%